Campus Canopy, 1970-04-01 - Campus Canopy, Valdosta State University (Valdosta State University, 1970)
Campus Canopy, vol. XXXV, no. 13, Valdosta State University
8 image scans, 1 pdf
Keywords: College student newspapers and periodicals -- Georgia -- Valdosta